Impact of COVID-19 on Neighborhood Social Support and Social Interactions in Umeå Municipality, Sweden - Zetterberg, Liv; Santosa, Ailiana; Ng, Nawi; Karlsson, Matilda; Eriksson, Malin (Frontiers in Sustainable Cities, 2021)
The objectives are to, for neighborhoods with different levels of social capital, (1) map out the levels of social interactions, emotional support, and instrumental support before the COVID-19 crisis, (2) analyze how social interactions, emotional support, and instrumental support had changed during the pandemic and, (3) analyze changes in self-rated health during the pandemic. This study is based on a telephone survey with a subsample of 168 respondents in Umeå municipality who participated in a large base-line social capital survey in 2006. We asked whether neighbors talk to, care for, and help each other, before and during the Covid crisis. Individuals rated their health as poor or good. We compared people's self-rated health and their perceptions about their neighborhoods between those who lived in high or low/medium social capital neighborhoods. Before the pandemic, participants in high social capital neighborhoods reported more active neighborhood interaction and support. During the crisis, social interaction and support increased in all neighborhoods, but more in high social capital neighborhoods. Overall, people seemed to help and care for each other more during than before the crisis. More individuals in the high social capital neighborhoods reported improvement in their health during the pandemic, than those in the low/medium social capital neighborhoods. Our findings indicate that neighborhoods social capital can be strengthened during a crisis, in particular in areas with existing high levels of social capital. The findings need to be interpreted carefully due to its small sample size but observed patterns warrant further investigation.